The Immunogenicity and Anti-tumor Efficacy of a Rationally Designed Neoantigen Vaccine for B16F10 Mouse Melanoma - Zhang, Yan; Lin, Zhibing; Wan, Yuhua; Cai, Huaman; Deng, Li; Li, Rongxiu (Frontiers in Immunology, 2019)
Tumor neoantigens are ideal targets for cancer immunotherapy as they are recognized by host immune system as foreigners and can elicit tumor-specific immune responses. However, existing strategies utilizing RNA or long peptides for the neoantigen vaccines render limited immune responses since only 20–30% of neoantigens predicted in silico to bind MHC I molecules are capable of eliciting immune responses with the majority of responding T cells are CD4+. Therefore, it warrants further exploration to enhance neoantigen-specific CD8+ T cells responses. Since neoantigens are naturally weak antigens, we asked whether foreign T help epitopes could enhance their immunogenicity. In present study, we chose 4 weak B16F10 neoantigens as vaccine targets, and fused them to the transmembrane domain of diphtheria toxin, namely DTT-neoAg. Strikingly, the vaccine elicited anti-tumor CD8+ T cells responses and enhanced tumor infiltration of both T cells and NK cells. Impressively, DTT-neoAg vaccine significantly deterred tumor growth with the inhibition rate reached 88% in the preventive model and 100% in the therapeutic model at low dose of tumor challenge. Furthermore, after second challenge with higher dose of tumor cells, 33.3% of the immunized mice remained tumor-free for 6 months in the therapeutic model. Because DTT is a non-toxic domain of diphtheria toxin, it may be not of great concern in terms of safety as a Th epitope provider. Thus, the fusion strategy employed by this study may become a feasible and powerful approach for development of personalized cancer vaccines.